A comprehensive study of the aerodynamic characteristics of an aspect ratio of 6.25:1 inclined square prism - Chen, Zengshun; Ning, Guoliang; Zhang, Likai; Li, Sijia; Wang, Siyu; Xu, Yemeng; Yuan, Chenfeng; Tse, T. K.; Li, Cruz Y.; Xue, Xuanyi (Frontiers in Physics, 2023)
Inclined prismatic structures have grown in popularity in civil engineering due to increased architectural and aesthetic demands, leading to a surging need to study their aerodynamic properties. In this study, an inclined 6.25:1 square prism was examined using wind tunnel tests and numerical simulations. The Synchronous Multi-Pressure Sensing System (SMPSS) wind tunnel technique was used to evaluate the aerodynamic characteristics of the structure, including surface pressure distribution, local force spectra, force coefficient, coherence, and the Strouhal number. Moreover, the numerical Large Eddy Simulations (LES) were also deployed to investigate the flow field morphology around the structure. Results show that the orientation, direction, and angle of inclination direction significantly affect the prism’s aerodynamic characteristics. Several flow field phenomena were also revealed. Forward inclination enhances the downwash flow, whereas the backward counterpart enhances the upwash flow, and transverse inclination produces a noticeable modification in the vortex morphology near the prism base. These findings can inform structural design and contaminant dispersion efforts.